Composite graphene conductive paste for battery and preparation method of composite graphene conductive paste
The modified surfactant is prepared by chemical modification and combined with other raw materials, and the problems of insufficient stability and poor adhesion of existing composite graphene conductive paste for batteries are solved, and excellent effects of conductivity, dispersion, stability and adhesion are achieved.
Patent Information
- Application Number
- CN202510212157.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The performance stability of the existing composite graphene conductive paste for batteries is insufficient, and long-term use will reduce the conductivity, and the adhesion to the material substrate is insufficient, which will affect the use effect.
The modified surfactant was prepared by chemical modification, and combined with graphene, carbon nanotubes, dispersants, stabilizers, solvents, silane coupling agent KH-550 and binder to obtain a composite graphene conductive paste for batteries with excellent conductivity, dispersion, stability and bonding.
It improves the conductivity, dispersion, stability and bonding properties of conductive pastes, ensures better application results in the battery field, and extends service life.
Smart Images

Figure SMS_7 
Figure SMS_8 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive materials, and in particular to a composite graphene conductive slurry for batteries and a preparation method thereof. Background Art
[0002] Composite graphene conductive slurry is a composite material formed by compounding graphene with other conductive materials (such as carbon black, carbon nanotubes, metal nanoparticles, etc.) and adding them to a conductive medium. It has the characteristics of excellent conductivity, good corrosion resistance and mechanical strength.
[0003] The patent with application number CN202111451171.2 discloses a conductive composite material, a conductive slurry and a preparation method for ion batteries. The method comprises: adding 1-20 parts by weight of graphene to 100-1000 parts by weight of a solvent containing a dispersant, mixing evenly to obtain a graphene dispersion; in an inert gas environment and a preset pressure condition, adding 20-100 parts by weight of a vinylidene fluoride monomer, 0.2-1 parts by weight of an initiator and 0.01-1 parts by weight of a pH adjuster to 20-100 parts by weight of the graphene dispersion, mixing evenly, polymerizing at low temperature, centrifuging and drying the polymerization product to obtain a polyvinylidene fluoride / graphene conductive composite material. The application can effectively improve the mechanical and electrical properties of the conductive composite material and the conductive slurry, thereby significantly optimizing the electrical performance of the ion battery; the patent with application number CN201 Patent No. 610616820.2 discloses a graphene conductive paste for lithium batteries and a preparation method thereof. The conductive paste is prepared from 10-15 parts of graphite powder, 0.5-2 parts of activator, 0.5-1 parts of dispersant, 0.2-0.3 parts of colloidal material, 0.1-0.5 parts of carbon nanotubes, 0.01-0.1 parts of promoter, 85-90 parts of solvent, and an appropriate amount of viscosity regulator. The graphite is refined and activated, and further peeled off by dispersion grinding, and the graphite is peeled off into graphene. At the same time, the micron-sized promoter and graphene and carbon nanotubes are interwoven by the colloidal material to form composite micro-particles during the grinding process. The composite micro-particles have excellent dispersibility and can improve the conductivity and discharge capacity of the battery active material. However, the performance stability of the above two conductive pastes is insufficient, and the conductive performance will be reduced after long-term use. In addition, the adhesion to the material base is insufficient during use, which affects the use effect.
[0004] Therefore, it is necessary to develop a composite graphene conductive slurry for batteries with excellent conductivity, dispersion, adhesion and stability, so that it can play a more important role in the battery field. Summary of the invention
[0005] The purpose of the present invention is to provide a composite graphene conductive slurry for battery and a preparation method thereof in view of the deficiencies in the prior art. The composite graphene conductive slurry for battery prepared by the present invention has excellent performance when applied to batteries.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A composite graphene conductive slurry for a battery comprises the following raw materials in parts by weight: 1-10 parts of graphene, 1-8 parts of carbon nanotubes, 0.5-1 parts of a dispersant, 0.5-2 parts of a stabilizer, 85-90 parts of a solvent, 0.5-1 parts of a silane coupling agent KH-550, 1-3 parts of a modified surfactant, and 0.5-1 parts of a binder; the preparation method of the modified surfactant is as follows: Step S1, mixing linolenic acid, glycidol and concentrated sulfuric acid uniformly, reacting at 90-100° C. with stirring for 6-8 hours, cooling to room temperature, and purifying to obtain intermediate 1; Step S2, adding intermediate 1 and m-aminobenzyl bromide to anhydrous ethanol at 70-90° C. with stirring, reacting for 2-4 hours, cooling to room temperature, and purifying to obtain intermediate 2; Step S3, mixing the intermediate 2, abietic acid and concentrated sulfuric acid uniformly, reacting at 90-100° C. with stirring for 6-8 hours, cooling to room temperature, and purifying to obtain a modified surfactant; The synthetic route of modified surfactant is as follows: ; ; .
[0007] Furthermore, in step S1, the mass ratio of linolenic acid, glycidol and concentrated sulfuric acid is 3:0.6-0.9:0.2-0.4.
[0008] Furthermore, in step S2, the mass ratio of the intermediate 1 to the m-aminobenzyl bromide is 4:2-3, and the amount of the added m-aminobenzyl bromide in anhydrous ethanol is 0.09-0.12 g / mL.
[0009] Furthermore, in step S3, the mass ratio of the intermediate 2, abietic acid and concentrated sulfuric acid is 5:2.5-3:0.2-0.4.
[0010] Furthermore, the dispersant is one or more of sodium stearate, polyvinyl alcohol, polyethylene imine, potassium p-sulfonate acetoacetanilide, and polyethylene glycol.
[0011] Furthermore, the stabilizer is one or more of sodium carboxymethyl cellulose, polyacrylic acid, and polyvinyl pyrrolidone.
[0012] Furthermore, the solvent is one or more of N-methylpyrrolidone, deionized water, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl succinate, dibutyl phthalate, ethanol, isopropanol, butanone, and toluene.
[0013] Furthermore, the adhesive is one or more of styrene-butadiene rubber, ethyl cellulose, polyvinylidene fluoride, and polytetrafluoroethylene.
[0014] The present invention also provides a method for preparing the composite graphene conductive slurry for the battery, comprising the following steps: (1) Graphene, carbon nanotubes, dispersant, stabilizer, modified surfactant, silane coupling agent KH-550, and binder are mixed and ball milled to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first mixed and then sand-milled to obtain a composite graphene conductive slurry for a battery.
[0015] The present invention has the following beneficial effects: The present invention adopts a chemical modification method to obtain a modified surfactant, and compounding the modified surfactant with other raw materials to obtain a composite graphene conductive paste for batteries with excellent conductivity, dispersibility, stability and adhesion. The synthesis of the modified surfactant firstly obtains intermediate 1 through an esterification reaction between the hydroxyl group of glycidol and the carboxyl group of linolenic acid, and introduces the epoxy group of glycidol into the structure of intermediate 1; then, an intermediate 2 containing a hydroxyl group is obtained through a ring-opening reaction between the amino group of m-aminobenzyl bromide and the epoxy group of intermediate 1; finally, an abietic acid group is introduced through an esterification reaction between the carboxyl group of abietic acid and the hydroxyl group of intermediate 2 to obtain a modified surfactant. The structure of the modified surfactant contains nitrogen, bromine and abietic acid groups. In the graphene conductive paste, the nitrogen element can improve the overall conductivity of the paste, and the introduction of the nitrogen element can optimize the graphene. The charge transfer path is improved, thereby increasing the charge migration rate and efficiency, which helps to improve the conductivity of graphene conductive paste in the battery field; bromine nitrogen compounds can improve the dispersion uniformity of the conductive paste by increasing the repulsive force between particles in the graphene conductive paste, thereby improving the stability of the paste, and bromine nitrogen compounds can improve the conductivity of the conductive paste, which is mainly because bromine and nitrogen elements have a promoting effect on the transmission of electrons, which can reduce the resistivity of the paste and improve the conductivity of the conductive paste; abietic acid groups help to enhance the adhesion between the graphene conductive paste and the surface of the coated object, ensuring that the conductive paste can be firmly attached to the substrate.
[0016] The present invention compounds graphene, carbon nanotubes, a dispersant, a stabilizer, a solvent, a modified surfactant, an adhesive and a silane coupling agent KH-550 to obtain a composite graphene conductive paste for a battery with excellent performance, wherein the modified surfactant itself can improve the dispersibility of the conductive paste, so that the conductive paste is not easy to agglomerate during use, thereby avoiding the adverse effect of agglomeration on the conductive efficiency, thereby improving the conductive performance of the conductive paste. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0018] The raw materials used in the following examples are all common commercial products. The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 1-30 nm and a length of 1-50 μm; the polyvinyl alcohol is polyvinyl alcohol 2488, purchased from Jinan Guangxun Trading Co., Ltd.; the viscosity of polyethyleneimine is 200-500 mPa·s and the molecular weight is 300; the molecular weight of polyethylene glycol is 400; sodium carboxymethyl cellulose has a viscosity of 50-100 mPa·s and a molecular weight of 90,000; the effective ingredient content of polyacrylic acid is 99%, purchased from Qingdao Baiyi Chemical Co., Ltd.; polyvinyl pyrrolidone is PVP K15 model was purchased from Lianyungang Ronghe New Material Technology Co., Ltd.; SBR1502 model was selected for styrene-butadiene rubber, purchased from Xiangmao International Trade (Changzhou) Co., Ltd.; N-20 model was selected for ethyl cellulose, with a mesh size of 100, purchased from Hebei Kelongduo Biotechnology Co., Ltd.; Arkema HSV900 model was selected for polyvinylidene fluoride, purchased from Shanghai Xinjihua Plastic Co., Ltd.; and PFA345X was selected from Chemours, USA, purchased from Dongguan Jiangyu New Materials Co., Ltd.
[0019] Example 1 A composite graphene conductive slurry for a battery, comprising the following raw materials in parts by weight: 1 part of graphene, 8 parts of carbon nanotubes, 0.5 parts of a dispersant, 0.5 parts of a stabilizer, 85 parts of a solvent, 0.5 parts of a silane coupling agent KH-550, 1 part of a modified surfactant, and 0.5 parts of a binder; The dispersant is sodium stearate, the stabilizer is sodium carboxymethyl cellulose, the solvent is N-methyl pyrrolidone, and the binder is styrene-butadiene rubber; The preparation method of the modified surfactant is as follows: Step S1, 3 g of linolenic acid, 0.6 g of glycidol and 0.2 g of concentrated sulfuric acid were uniformly mixed, reacted at 90° C. with stirring for 8 h, cooled to room temperature, and then extracted with 20 mL of ethyl acetate, and the organic phase was distilled under reduced pressure to obtain intermediate 1; Step S2, adding 4 g of intermediate 1 and 2 g of m-aminobenzyl bromide to 22.22 mL of anhydrous ethanol at 70° C. with stirring, reacting for 4 h, cooling to room temperature, and drying in a vacuum drying oven at 40° C. to constant weight to obtain intermediate 2; Step S3, 5 g of intermediate 2, 2.5 g of abietic acid and 0.2 g of concentrated sulfuric acid were mixed evenly, reacted at 90° C. with stirring for 8 h, cooled to room temperature, and then extracted with 20 mL of ethyl acetate, and the organic phase was distilled under reduced pressure to obtain a modified surfactant.
[0020] The synthetic route of modified surfactant is as follows: ; ; .
[0021] The NMR results of the modified surfactant are: 1 H NMR (300MHz, acetone-d6) δ 9.53 (s, 1H), 7.17 (t, 1H), 6.86 (s, 1H), 6.70 (d, 1H), 6.44 (t, 1H), 5.75 (s, 1H), 5.21-5.50 (m, 8H), 4.56 (s, 2H), 4.17-4. 42 (m, 2H), 3.15-3.40 (m, 2H), 2.80 (t, 4H), 2.32-2.42 (m, 5H), 1.94-2.19 (m, 7H), 1.12-2.01 (m, 25H), 0.78-0.86 (m, 9H).
[0022] A method for preparing a composite graphene conductive slurry for a battery comprises the following steps: (1) Graphene, carbon nanotubes, dispersant, stabilizer, modified surfactant, silane coupling agent KH-550 and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a mixer, stirred at 1000 rpm for 5 min, and then placed in a sand mill at a frequency of 30 Hz for 2 h to obtain a composite graphene conductive slurry for battery.
[0023] Example 2 A composite graphene conductive slurry for a battery, comprising the following raw materials in parts by weight: 10 parts of graphene, 1 part of carbon nanotubes, 2 parts of dispersant, 2 parts of stabilizer, 90 parts of solvent, 1 part of silane coupling agent KH-550, 3 parts of modified surfactant, and 1 part of adhesive; The dispersant is polyvinyl alcohol, the stabilizer is sodium carboxymethyl cellulose, the solvent is toluene, and the binder is ethyl cellulose; The preparation method of the modified surfactant is as follows: Step S1, 3 g of linolenic acid, 0.9 g of glycidol and 0.4 g of concentrated sulfuric acid were mixed evenly, reacted at 100° C. with stirring for 6 h, cooled to room temperature, and then extracted with 20 mL of ethyl acetate, and the organic phase was distilled under reduced pressure to obtain intermediate 1; Step S2, adding 4 g of intermediate 1 and 3 g of m-aminobenzyl bromide to 25 mL of anhydrous ethanol at 90° C. with stirring, reacting for 2 h, cooling to room temperature, and drying in a vacuum drying oven at 40° C. to constant weight to obtain intermediate 2; Step S3, 5 g of intermediate 2, 3 g of abietic acid and 0.4 g of concentrated sulfuric acid were mixed evenly, reacted at 100° C. with stirring for 6 h, cooled to room temperature, and then extracted with 20 mL of ethyl acetate, and the organic phase was distilled under reduced pressure to obtain a modified surfactant.
[0024] A method for preparing a composite graphene conductive slurry for a battery comprises the following steps: (1) Graphene, carbon nanotubes, dispersant, stabilizer, modified surfactant, silane coupling agent KH-550 and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a mixer, stirred at 1000 rpm for 5 min, and then placed in a sand mill at a frequency of 30 Hz for 2 h to obtain a composite graphene conductive slurry for battery.
[0025] Example 3 A composite graphene conductive slurry for a battery, comprising the following raw materials in parts by weight: 7 parts of graphene, 5 parts of carbon nanotubes, 1 part of a dispersant, 1 part of a stabilizer, 87 parts of a solvent, 0.8 parts of a silane coupling agent KH-550, 2 parts of a modified surfactant, and 0.7 parts of a binder; The dispersant is polyethylene glycol, the stabilizer is polyacrylic acid, the solvent is dimethyl succinate, and the binder is polytetrafluoroethylene; The preparation method of the modified surfactant is as follows: Step S1, 3 g of linolenic acid, 0.8 g of glycidol and 0.3 g of concentrated sulfuric acid were uniformly mixed, reacted at 95° C. with stirring for 7 h, cooled to room temperature, and then extracted with 20 mL of ethyl acetate, and the organic phase was distilled under reduced pressure to obtain intermediate 1; Step S2, adding 4 g of intermediate 1 and 2.5 g of m-aminobenzyl bromide to 25 mL of anhydrous ethanol at 80° C. with stirring, reacting for 3 h, cooling to room temperature, and drying in a vacuum drying oven at 40° C. to constant weight to obtain intermediate 2; Step S3, 5 g of intermediate 2, 2.7 g of abietic acid and 0.3 g of concentrated sulfuric acid were mixed evenly, reacted at 95° C. with stirring for 7 h, cooled to room temperature, and then extracted with 20 mL of ethyl acetate, and the organic phase was distilled under reduced pressure to obtain a modified surfactant.
[0026] A method for preparing a composite graphene conductive slurry for a battery comprises the following steps: (1) Graphene, carbon nanotubes, dispersant, stabilizer, modified surfactant, silane coupling agent KH-550 and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a mixer, stirred at 1000 rpm for 5 min, and then placed in a sand mill at a frequency of 30 Hz for 2 h to obtain a composite graphene conductive slurry for battery.
[0027] Comparative Example 1 A composite graphene conductive slurry for a battery, comprising the following raw materials in parts by weight: 6 parts of graphene, 4 parts of carbon nanotubes, 1 part of a dispersant, 0.5 parts of a stabilizer, 85 parts of a solvent, 0.5 parts of a silane coupling agent KH-550, 1 part of a modified surfactant, and 1 part of a binder; The dispersant is polyethylene glycol, the stabilizer is polyacrylic acid, the solvent is dimethyl succinate, and the binder is polytetrafluoroethylene; The preparation method of the modified surfactant is as follows: Step S1, 3 g of linolenic acid, 0.8 g of glycidol and 0.3 g of concentrated sulfuric acid were uniformly mixed, reacted at 95° C. with stirring for 7 h, cooled to room temperature, and then extracted with 20 mL of ethyl acetate, and the organic phase was distilled under reduced pressure to obtain intermediate 1; Step S2, adding 4 g of intermediate 1 and 2.5 g of m-aminobenzyl bromide to 25 mL of anhydrous ethanol at 80° C. with stirring, reacting for 3 h, cooling to room temperature, and drying in a vacuum drying oven at 40° C. to constant weight to obtain a modified surfactant.
[0028] A method for preparing a composite graphene conductive slurry for a battery comprises the following steps: (1) Graphene, carbon nanotubes, dispersant, stabilizer, modified surfactant, silane coupling agent KH-550 and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a mixer, stirred at 1000 rpm for 5 min, and then placed in a sand mill at a frequency of 30 Hz for 2 h to obtain a composite graphene conductive slurry for battery.
[0029] Comparative Example 2 A composite graphene conductive slurry for a battery, comprising the following raw materials in parts by weight: 6 parts of graphene, 1 part of carbon nanotubes, 0.3 parts of a dispersant, 0.4 parts of a stabilizer, 85 parts of a solvent, 0.5 parts of a silane coupling agent KH-550, 1 part of a surfactant, and 0.7 parts of a binder; The dispersant is polyethylene glycol, the stabilizer is polyacrylic acid, the solvent is dimethyl succinate, the binder is polytetrafluoroethylene, and the surfactant is linolenic acid; A method for preparing a composite graphene conductive slurry for a battery comprises the following steps: (1) Graphene, carbon nanotubes, dispersant, stabilizer, surfactant, silane coupling agent KH-550 and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a mixer, stirred at 1000 rpm for 5 min, and then placed in a sand mill at a frequency of 30 Hz for 2 h to obtain a composite graphene conductive slurry for battery.
[0030] Comparative Example 3 A composite graphene conductive slurry for a battery, comprising the following raw materials in parts by weight: 0.5 parts of graphene, 1 part of carbon nanotubes, 0.3 parts of a dispersant, 0.4 parts of a stabilizer, 85 parts of a solvent, 0.5 parts of a silane coupling agent KH-550, and 0.7 parts of a binder; The dispersant is polyethylene glycol, the stabilizer is polyacrylic acid, the solvent is dimethyl succinate, and the binder is polytetrafluoroethylene; A method for preparing a composite graphene conductive slurry for a battery comprises the following steps: (1) Graphene, carbon nanotubes, dispersant, stabilizer, silane coupling agent KH-550 and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a mixer, stirred at 1000 rpm for 5 min, and then placed in a sand mill at a frequency of 30 Hz for 2 h to obtain a composite graphene conductive slurry for battery.
[0031] The performance of the composite graphene conductive slurry for batteries prepared in Examples 1-3 and Comparative Examples 1-3 was tested. The test method is as follows. The test results are shown in Tables 1 and 2 below.
[0032] (1) Adhesion Adhesion was measured according to GB / T17473.4-2008.
[0033] (2) Viscosity The test was carried out according to the rotational viscometer method described in DB13 / T5026.1-2019.
[0034] (3) Conductive properties The square resistance was measured according to GB / T17473.3-2008.
[0035] (4) Dispersion performance The fineness is measured according to GB / T17473.2-2008.
[0036] (5) Stability The viscosity and square resistance of the composite graphene conductive paste after being placed for 1 day and 180 days were tested. Specifically, after being placed for 1 day, the conductive paste on the top was taken to test the viscosity, and then it was placed in an ordinary indoor environment for 180 days. After being placed for 180 days, the same volume of conductive paste was taken from the same position to measure the viscosity and square resistance of the conductive paste.
[0037] Table 1 Adhesion, viscosity, conductivity, dispersion and corrosion resistance tests of composite graphene conductive slurry for batteries
[0038] Table 2 Stability test of composite graphene conductive slurry for battery
[0039] It can be seen from Table 1 and Table 2 that the performance of the composite graphene conductive paste for batteries prepared in Examples 1-3 is more excellent. As shown in Table 1, compared with Comparative Examples 1-3, the composite graphene conductive paste for batteries prepared in Examples 1-3 has excellent adhesion and suitable viscosity. The adhesion can ensure that the conductive paste is closely adhered to the surface of the substrate, and the appropriate viscosity gives the conductive paste good fluidity, so that it can be evenly coated; the composite graphene conductive paste for batteries prepared in Examples 1-3 has a small square resistance, good conductivity, and can effectively transfer current, which can optimize the conductive performance of the product and improve the quality of the product; the composite graphene conductive paste for batteries prepared in Examples 1-3 has a small fineness, indicating that the contact area between the conductive paste particles is large, the conductive paths are dense, and the conductive performance is improved. In addition, the conductive paste has a small fineness, is evenly dispersed, is not easy to precipitate and agglomerate during storage, and has better stability. It can be seen from Table 2 that compared with Comparative Examples 1-3, the composite graphene conductive slurry for batteries prepared in Examples 1-3 has better stability. The stable conductive slurry can ensure that its conductive performance remains constant during long-term use, thereby extending the service life of the product.
[0040] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0041] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A composite graphene conductive slurry for battery, characterized in that: The invention comprises the following raw materials in parts by weight: 1-10 parts of graphene, 1-8 parts of carbon nanotubes, 0.5-1 parts of dispersant, 0.5-2 parts of stabilizer, 85-90 parts of solvent, 0.5-1 parts of silane coupling agent KH-550, 1-3 parts of modified surfactant, and 0.5-1 parts of adhesive; the preparation method of the modified surfactant is as follows: Step S1, linolenic acid, glycidol and concentrated sulfuric acid are mixed uniformly, reacted at 90-100° C. with stirring for 6-8 hours, cooled to room temperature, and purified to obtain intermediate 1. The structural formula of intermediate 1 is: ; Step S2, adding intermediate 1 and m-aminobenzyl bromide to anhydrous ethanol at 70-90° C. with stirring, reacting for 2-4 hours, cooling to room temperature, and purifying to obtain intermediate 2. The structural formula of intermediate 2 is: ; Step S3, the intermediate 2, abietic acid and concentrated sulfuric acid are uniformly mixed, reacted at 90-100° C. with stirring for 6-8 hours, cooled to room temperature, purified, and a modified surfactant is obtained. The structural formula of the modified surfactant is: 。 2. The composite graphene conductive slurry for battery according to claim 1, characterized in that: The mass ratio of linolenic acid, glycidol and concentrated sulfuric acid in step S1 is 3:0.6-0.9:0.2-0.
4.
3. The composite graphene conductive slurry for battery according to claim 1, characterized in that: The mass ratio of the intermediate 1 to the m-aminobenzyl bromide in step S2 is 4:2-3, and the amount of the added m-aminobenzyl bromide in anhydrous ethanol is 0.09-0.12 g / mL.
4. The composite graphene conductive slurry for battery according to claim 1, characterized in that: The mass ratio of the intermediate 2, abietic acid and concentrated sulfuric acid in step S3 is 5:2.5-3:0.2-0.
4.
5. The composite graphene conductive slurry for battery according to claim 1, characterized in that: The dispersant is one or more of sodium stearate, polyvinyl alcohol, polyethylene imine, potassium p-sulfonate acetoacetanilide, and polyethylene glycol.
6. The composite graphene conductive slurry for battery according to claim 1, characterized in that: The stabilizer is one or more of sodium carboxymethyl cellulose, polyacrylic acid and polyvinyl pyrrolidone.
7. The composite graphene conductive slurry for battery according to claim 1, characterized in that: The solvent is one or more of N-methylpyrrolidone, deionized water, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl succinate, dibutyl phthalate, ethanol, isopropanol, butanone and toluene.
8. The composite graphene conductive slurry for battery according to claim 1, characterized in that: The adhesive is one or more of styrene-butadiene rubber, ethyl cellulose, polyvinylidene fluoride and polytetrafluoroethylene.
9. A method for preparing the composite graphene conductive slurry for battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Graphene, carbon nanotubes, dispersant, stabilizer, modified surfactant, silane coupling agent KH-550, and binder are mixed and ball milled to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first mixed and then sand-milled to obtain a composite graphene conductive slurry for a battery.
Citation Information
Patent Citations
A graphene conductive paste for lithium batteries and its preparation method
CN106207094B
Conductive composite materials, conductive pastes and preparation methods for ion batteries
CN114085339B
Conductive silver paste, preparation method and application thereof
CN110504046A
High-solid-content graphene composite conductive paste, preparation method and application thereof
CN115101750A
Glass powder composition, glass powder, conductive silver paste and solar cell
CN116332518A
Cited By
High-dispersion graphene conductive adhesive solution for battery and preparation method of high-dispersion graphene conductive adhesive solution
CN120432540A
A highly dispersed graphene conductive adhesive for batteries and preparation method thereof
CN120432540B